Impact of sex and APOE E4 on age‐related cerebral blood flow trajectories in cognitively asymptomatic middle‐aged and older adults: A longitudinal study: Neuroimaging / Normal brain aging. (7th December 2020) - Wang, Rui; Oh, Jennifer M.; Motovylyak, Alice; Ma, Yue; Sager, Mark A.; Rowley, Howard A.; Johnson, Kevin M.; Gallagher, Catherine L.; Carlsson, Cynthia M.; Bendlin, Barbara B; Johnson, Sterling C.; Asthana, Sanjay; et al.
Abstract: Background: Reduced cerebral blood flow (CBF) has been considered as a potentially early biomarker of late‐onset Alzheimer's disease (AD). We sought to detect the pattern of age‐related CBF trajectories, and to investigate how these trajectories are affected by APOE, chromosomal sex, and cardiometabolic measurements. Method: From two ongoing longitudinal cohort studies—the Wisconsin Registry for Alzheimer's Prevention and the Wisconsin Alzheimer's Disease Research Center—we included 950 individuals (age range 40—89 years), who were cognitively unimpaired at their first visit. CBF was measured using pseudo‐continuous arterial spin labeling MRI. Demographic factors, APOE ɛ4 status, and cardiometabolic measurements were obtained during a clinic visit that included structured interviews, physical examinations, and blood sampling. We applied linear mixed‐effects models in our analyses, which focused on brain regions of relevance to AD. Result: During the follow‐up period (median 2.17 years, range 0.13—8.24 years), increasing age was significantly associated with decreasing CBF in total gray matter (β=‐1.54) (Figure, a), hippocampus (‐1.33), superior frontal gyrus (‐1.92), middle frontal gyrus (‐2.20), posterior cingulate (‐2.71), and precuneus (‐2.32), with all p‐values<0.01. A three‐way interactive effect of age, sex, and APOE ɛ4 allele was observed on CBF trajectories. That is, compared with male ɛ4 carriers, female ɛ4 carriers showed a faster decline in global and regional CBF with increasing age (Figure, c), whereas age‐related decline in CBF was similar between male and female ɛ4 non‐carriers (Figure, b). Worse cardiometabolic profile (i.e., increased systolic blood pressure, body mass index, total cholesterol, and blood glucose) was associated with lower CBF at all the visits. When time‐varying cardiometabolic measurements were adjusted in the model, the synergistic effect of sex and APOE ɛ4 on age‐related CBF trajectories became largely attenuated. Conclusion: Our findings demonstrate that APOE genotype and sex interactively impact CBF trajectories across the lifespan, and that this effect may be partially explained by cardiometabolic alterations.